Pengembangan Kawasan Eduwisata Rajendra Farm Dusun Trayu sebagai Eduwisata Internasional: Indonesia - Firdaus, Ad Zulfa Geofani; Yendrawati, Reni (UII, 2025)
The development of the Rajendra Farm educational tourism area in Dusun Trayu as an international educational tourism destination is a strategic step in promoting sustainable tourism and education in Indonesia. Dusun Trayu, located in an underdeveloped area, has great potential to become a center for learning about nature and culture, attracting both local and international tourists. This study aims to outline some key aspects of the development of the Rajendra Farm educational tourism area in Dusun Trayu as an international educational tourism destination. Rajendra Farm was initiated by Mr. Heri Kurniawan in 2008, initially as a small-scale sheep farm. This sheep farm continued to develop and underwent its fair share of ups and downs until 2016 when it finally established a successful farming system. From that point on, it was able to collaborate with livestock organizations in Yogyakarta. Rajendra Farm has since partnered with Karang Taruna Trayu, Ngargosari Tourist Village, the Ministry of Agriculture, and Jalaluddin. Its primary goal is to facilitate qurban (sacrificial) activities. As the business evolved, Rajendra Farm expanded into educational tourism related to sheep farming. However, this educational tourism was incomplete due to a lack of glamping facilities, photography spots, restaurants, and souvenir shops. Therefore, as a civil engineering student, the author assisted Rajendra Farm in developing its educational tourism, particularly in designing a restaurant. Based on the existing conditions at Rajendra Farm, which already had foundations, floor slabs, columns, and a roof in place, the author created a 3D restaurant design to provide a visual representation of the restaurant that will be built at Rajendra Farm.